A COMPARATIVE STUDY OF THE LEVEL OF ADMINISTRATIVE EMPOWERMENT OF SUPERVISORS IN THE PRIMARY AND SECONDARY STAGES, IN THE SPECIALIZATIONS OF PHYSICAL EDUCATION AND ADMINISTRATIVE SUPERVISOR IN THE SOUTHERN GOVERNORATES - Ali, Fouad Abdul Mahdi Mahmoud; Amin, Hutham Abdul-Amir (Universitas Negeri Jakarta, 2026)
Background. Comparison between supervisors specializing in physical education and administrative supervisors in terms of administrative empowerment level. Comparison between supervisors specializing in physical education and administrative supervisors for primary and secondary levels in terms of administrative empowerment. Empowering supervisors administratively is one of reasons for success in educational and sports work in general, and administrative work in particular, due to it has a direct impact on supervisor's personality and resulting impact on supervisor's behavior and personality. Objectives. This study aims to building a managerial empowerment scale for sports supervisors and administrative supervisors in Southern governorates. Identifying level of administrative empowerment of sports supervisors and administrative supervisors for primary and secondary levels. Method The researchers used descriptive approach, survey method, and correlational studies because it is the most suitable for nature of solving problem and achieving research objectives. Population included physical education specialists and administrative supervisors for the primary and secondary levels in the southern governorates (Basra, Maysan,Dhi Qar, and Muthanna), totaling (189) individuals. Results Results shows administration supervisors enjoyed a greater level of administrative empowerment than supervisors specializing in physical education for the entire sample. Secondary school supervisors enjoy a greater level of administrative empowerment than primary school supervisors do. Conclusion. Recommendation is to relying on administrative empowerment scale for administrative supervisors and specialization in physical education to measure their level of empowerment in southern governorates (Basra – Maysan – Dhi Qar – Muthanna). Emphasizing that officials in educational process pay attention to administrative empowerment of supervisors specializing in physical education and administrative supervisors by increasing their delegation of authority and their participation in decision-making process, especially primary school supervisors.